2021
DOI: 10.1029/2020wr028091
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does Hydrological Science Play in the Age of Machine Learning?

Abstract: This paper is derived from a keynote talk given at the Google's 2020 Flood Forecasting Meets Machine Learning Workshop. Recent experiments applying deep learning to rainfall-runoff simulation indicate that there is significantly more information in large-scale hydrological data sets than hydrologists have been able to translate into theory or models. While there is a growing interest in machine learning in the hydrological sciences community, in many ways, our community still holds deeply subjective and nonevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(189 citation statements)
references
References 114 publications
(195 reference statements)
5
183
0
1
Order By: Relevance
“…Indeed it has been suggested that machine learning method might be more successful in converting rainfalls into streamflows than models based on process representations (e.g., Kratzert et al, 2019; Nearing et al, 2021). Such data‐based methods are heavily dependent on the range and quality of the training data set available, though they will be able to compensate for inconsistencies in a data set if those inconsistencies show some form of consistent structure (see the discussion in Beven, 2020b).…”
Section: Issues In Generating Inputs For Rainfall‐runoff Modelsmentioning
confidence: 99%
“…Indeed it has been suggested that machine learning method might be more successful in converting rainfalls into streamflows than models based on process representations (e.g., Kratzert et al, 2019; Nearing et al, 2021). Such data‐based methods are heavily dependent on the range and quality of the training data set available, though they will be able to compensate for inconsistencies in a data set if those inconsistencies show some form of consistent structure (see the discussion in Beven, 2020b).…”
Section: Issues In Generating Inputs For Rainfall‐runoff Modelsmentioning
confidence: 99%
“…parametric). These limitations are especially severe for hydrologic models of Earth's water cycle extremes and their impacts (Nearing et al, 2021). Data-driven knowledge acquisition could help to identify and reduce these model biases (structural errors) thus improving the model predictability.…”
Section: Science Challengementioning
confidence: 99%
“…parametric). These limitations are especially severe for hydrologic models of Earth's water cycle extremes and their impacts (Nearing et al, 2021). Data-driven knowledge acquisition could help to identify and reduce these model biases (structural errors) thus improving the model predictability.Earth scientists have abundant physics-based experimental data (both observational and simulated), but they do not yet know how to discover and extract predictive knowledge from these large heterogenous dynamic data streams.…”
mentioning
confidence: 99%
“…Given the complexity of hydrobiogeochemical data and processes that occur across scales and compartments of a watershed, this strategy holds significant promise for advancing predictive understanding of watershed hydrobiogeochemical behavior. Nearing, Kratzert, et al (2020) advocated the importance of integrating ML into hydrological workflows.…”
Section: Watershed Hydrobiogeochemical Modelingmentioning
confidence: 99%